Doing business successfully in China - Chung, Mona (Chandos Asian studies series., 2011)
Despite the overwhelming importance of the Chinese economy to the success of Western economies, there has yet to be an examination of why Western companies have had difficulties in doing business with the Chinese. A significant barrier that companies have difficulty to overcome is the effective communication with their Chinese counter parts. This major impediment is caused by no understanding of the cultural differences between the Chinese and Western business cultures. This book offers the solution to this problem: the bi-cultural personnel. The first book presented by a true bi-cultural consultant and researcher who has depth knowledge in the understanding of both the Australian and Chinese markets, culture and more importantly the behavioural pattern of people from both sides of the businessesProvides a totally new perspective for business managers and entrepreneurs to find out how to avoid the same fate as has befallen so many failed enterprisesThe new perspective is to highlight the acceptance of cultural differences as the focus for devising and implementing successful strategy.